2009
DOI: 10.1590/s1678-77572009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic agreement between panoramic radiographs and color doppler images of carotid atheroma

Abstract: The aim of this study was to investigate the agreement between diagnoses of calcified atheroma seen on panoramic radiographs and color Doppler images. Our interest stems from the fact that panoramic images can show the presence of atheroma regardless of the level of obstruction detected by color Doppler images. Panoramic and color Doppler images of 16 patients obtained from the archives of the Health Department of the city of Valença, RJ, Brazil, were analyzed in this study. Both sides of each patient were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 23 publications
(41 reference statements)
0
32
0
18
Order By: Relevance
“…7,8 Confirmation of the presence of such lesions by ultrasound demonstrates that panoramic imaging is highly accurate with an 80% sensitivity, 81% specificity and 81% accurancy. 9,10 The purpose of this study was to investigate whether CCAP on panoramic images of older white and black females is related to low BMD on DXA. We hypothesized that white females and possibly black females with CCAP on the panoramic images would have greater evidence of osteopenia on their DXA scan than females free of CCAP on their images.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Confirmation of the presence of such lesions by ultrasound demonstrates that panoramic imaging is highly accurate with an 80% sensitivity, 81% specificity and 81% accurancy. 9,10 The purpose of this study was to investigate whether CCAP on panoramic images of older white and black females is related to low BMD on DXA. We hypothesized that white females and possibly black females with CCAP on the panoramic images would have greater evidence of osteopenia on their DXA scan than females free of CCAP on their images.…”
Section: Introductionmentioning
confidence: 99%
“…18 In a study conducted by Romano Sousa et al showed that there was a high level of agreement between diagnosis of calcified carotid atheromas seen on panoramic radiographs and color Doppler images with a k ¼ 0.78. 12 According to these studies panoramic radiographs had low to moderate specificity and low positive predictive value. In our study however panoramic radiography has 76% sensitivity at detecting calcified carotid artery atheromatous plaques.…”
Section: Evaluation Of Carotid Artery Atheromatous Plaquesmentioning
confidence: 95%
“…These plaques become thick, may suffer calcification and project themselves into the vessel lumen, determining blood flow change (1,2,3). Panoramic Radiographs help us to a diagnostic and detecting common carotid artery calcifications and the early diagnosis can be decrease the morbidity and mortality for subjects with common carotid artery calcifications .…”
Section: Introductionmentioning
confidence: 99%